Konstruksi Gaya Hidup Generasi Z dalam Praktik Kuliner: Studi di Kawasan Blok M - Febriani, Rizka; Budiasa, Meistra (Jurnal Ragam Pengabdian, 2026)
The rapid growth of digital media has transformed how Generation Z discovers, consumes, and shares culinary experiences, influencing their lifestyle. Blok M has emerged as a popular culinary destination and social space among Generation Z. This study analyzes the construction of Generation Z's lifestyle through culinary practices in the Blok M area. A qualitative approach based on the social construction theory of Peter L. Berger and Thomas Luckmann was employed. Data were collected through in-depth interviews, observation, and documentation involving 11 purposively selected Generation Z informants who had visited Blok M. Data were analyzed using reduction, display, and conclusion drawing techniques. The findings reveal that Generation Z's culinary lifestyle is constructed through digital media, spatial experiences, and social interaction. Platforms such as TikTok and Instagram stimulate visits through viral content, electronic word of mouth (e-WOM), Fear of Missing Out (FOMO), and peer recommendations. After visiting, participants share their experiences on social media as a form of self-representation. Furthermore, Blok M functions not only as a culinary destination but also as a social space where Generation Z gathers, interacts, builds relationships, and spends leisure time. These findings indicate that culinary practices in Blok M extend beyond food consumption, reflecting a digitally mediated lifestyle shaped by social interaction and meaningful spatial experiences.